Experimental Investigation of a Novel Extracting Water System from Air by Soil Cold Source. (28th November 2021) - Yao, Jianan; Wang, Xingtian; Zhu, Junfeng; Wang, Binbin; Niu, Junkui
Abstract : The distribution of fresh water resources is extremely uneven at home and abroad, and the air contains a large amount of water vapor that can be used, so air water has been a widespread concern. Air condensation method is simple and efficient and has strong water intake capacity, but it often needs to consume huge energy. Therefore, this work proposes a new simple and innovative method of drawing water from the air, based on extracting water from air process achieved by using the soil as the cold source. The new type of ground cold air water intake system is designed by the new innovative method, which uses the soil with constant temperature as the cold source to reduce energy consumption. By comparing the central composite design experiment with the field experiment and analyzing the condensate water and outlet temperature under different wind speed and humidity conditions, the quadratic equation expression of condensate water and outlet temperature is obtained, and the optimal import wind speed range under a certain humidity range is obtained according to the mathematical model. The experimental results show that the heat transfer effect between air and soil is ideal, the water intake can reach 2.2 kg in 20-hour continuous collection experiment, the air temperature is close to the soil temperature after cooling, and the effect of water intake is good, which confirms the feasibility of soil as a cold source of air condensation.